2017
DOI: 10.1007/s00203-016-1334-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in different compartments of an aquaponics system

Abstract: Aquaponics is a solution for sustainable production of fish and plants in a single semi-closed system, where nutrient-rich water from the aquaculture provides nutrients for plant growth. We examined the microbial communities within an experimental aquaponics system. Whereas the fish feces contained a separate community dominated by bacteria of the genus Cetobacterium, the samples from plant roots, biofilter, and periphyton were more similar to each other, while the communities were more diverse. Detailed exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
124
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 28 publications
19
124
1
Order By: Relevance
“…Since microorganisms are ubiquitous, they play an important part in all stages of aquaponic production. The influence of environmental conditions on their abundance, diversity and roles could be investigated, e.g., by further using Novel Generation of Sequencing Methods [26,27]. One of the central questions is appropriate pest and disease control.…”
Section: Trends In Technologymentioning
confidence: 99%
“…Since microorganisms are ubiquitous, they play an important part in all stages of aquaponic production. The influence of environmental conditions on their abundance, diversity and roles could be investigated, e.g., by further using Novel Generation of Sequencing Methods [26,27]. One of the central questions is appropriate pest and disease control.…”
Section: Trends In Technologymentioning
confidence: 99%
“…A recent metagenomics study [23] that studied the same aquaponics unit showed that in the system, only a low amount of lactic acid bacteria was present, however a much larger number of pseudomonads. It also shows that the enrichment step on King's B medium is very effective, as in the fish faeces community sampled during the metagenomics study, only a small number of pseudomonads were present.…”
Section: Discussionmentioning
confidence: 99%
“…It also shows that the enrichment step on King's B medium is very effective, as in the fish faeces community sampled during the metagenomics study, only a small number of pseudomonads were present. On the other hand, bacteria closely related to or formerly named Pseudomonas were present in large amounts [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations